Please I need you to show work
X - 5x + 52= 23
The first thing you need to do is recognize that X is the same thing as 1X. So we can rewrite the equation like this:
1X-5X+52=23 Now subtract 5X from 1X which would give us -4X
-4X +52=23 Now let's move the 52 by subtracting 52 from each side of the equation. We can manipulate any equation as long as we do so on both sides of the equation. Like this:
-4X+52-52=23-52 All we have to do know is solve the portions of the equation that we know.
52-52=0 and 23-52=-29 so we would end up with:
-4X=-29 Now we divide each side by -4
-4X/-4=-29/-4 Which would give us:
I hope this made sense, if there is any part of this you don't understand, let me know and I will explaing it further.
Here is a similar problem showing each step.
x-7x + 30 = 6 equation (1)
Step one is to get all your whole numbers (ex: 2, 10, -4,...) on one side of the equal sign and #x's (ex: 1x, 3x, -8x, -20x,...) on the other side of the equal sign.
In equation (1) l am going to choose to put the whole numbers on the right side of the equal sign. That means I need to move the + 30 to the right side. I can accomplish this by subtracting 30 from both sides of the equal sign.
x - 7x + 30 -30 = 6 -30 equation (2)
Now because + 30 -30 = 0 and 6 - 30 = -24 equation (2) can now be written as
x - 7x = -24 equation (3)
We now have all the #x's on the left side of the equation and the whole numbers on the right side.
The next goal is to take x - 7x and turn it into one #x.
One way to do this is to look at x - 7x and think I have one x minus seven x. So one x minus seven x equals negative six x. 1x - 7x = -6x It is similar to saying 1 -7 = -6 you just have to remember that because you have 1x and -7x that your answer -6 better have an x with it as well.
So x - 7x = -24 now becomes
-6x = -24 equation (4)
The last step is to get x completely alone. This is done by dividing both sides of the equation (4) by -6.
-6/-6 = 1 and -24/-6 = 4
So we can write 1x = 4 and we have now solved for x.
If you want to make sure x = 4 is the right answer plug it into equation (1) and carry out math steps. You should get 6 = 6